2002
DOI: 10.1073/pnas.042683899
|View full text |Cite
|
Sign up to set email alerts
|

HOX genes in the sepiolid squid Euprymna scolopes : Implications for the evolution of complex body plans

Abstract: Molluscs display a rich diversity of body plans ranging from the wormlike appearance of aplacophorans to the complex body plan of the cephalopods with highly developed sensory organs, a complex central nervous system, and cognitive abilities unrivaled among the invertebrates. The aim of the current study is to define molecular parameters relevant to the developmental evolution of cephalopods by using the sepiolid squid Euprymna scolopes as a model system. Using PCR-based approaches, we identified one anterior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 54 publications
2
44
1
Order By: Relevance
“…Callaerts et al, 2002) but also in nemerteans (Kmita-Cunisse et al, 1998) or brachiopods (de Rosa et al, 1999). Yet, so far, the genomic organization of only a flatworm (see above) and the annelid polychaete Platynereis is known, and these probably contain a rather intact cluster (D. Ferrier, personal communication).…”
Section: There Are Clusters and Clustersmentioning
confidence: 99%
“…Callaerts et al, 2002) but also in nemerteans (Kmita-Cunisse et al, 1998) or brachiopods (de Rosa et al, 1999). Yet, so far, the genomic organization of only a flatworm (see above) and the annelid polychaete Platynereis is known, and these probably contain a rather intact cluster (D. Ferrier, personal communication).…”
Section: There Are Clusters and Clustersmentioning
confidence: 99%
“…Degnan & Morse (1993) revealed that there were five Hox genes in the abalone Haliotis rufescens, which is considered a relatively basal species in Gastropoda (see also Giusti et al, 2000;Hinman et al, 2003). Callaerts et al (2002) described nine Hox genes in the squid Euprymna scolopes, also inferring that a molluscan genome has only one Hox cluster. de Rosa et al (1999) compared Hox genes among various bilaterian animals, using the limpet Patella vulgata with six Hox genes as the molluscan representative, whereas Balavoine, de Rosa & Adoutte (2002), in a review paper, used the squid E. scolopes with nine Hox genes as the molluscan representative.…”
Section: Introductionmentioning
confidence: 99%
“…Vox2 shows a higher level of homology with Drosophila, mouse or human Pb homeodomains (they diverge by 0% and 9% respectively). The identification of proboscipedia orthologs from molluscs has proven difficult (Callaerts et al, 2002) although a study of the gastropod Haliotis suggested the presence of a Hox2 paralog (Degnan and Morse, 1993); in fact, Vox1 and Vox2 display significant similarity to the Hrox3 and 5 sequences. Alignment of the Vox4 and Vox5-derived amino acid sequences reveals the greatest similarity to members of the Cad protein family (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Cad function in Drosophila and its expression pattern in vertebrates indicate that this gene family is important in the axial pattern formation (Epstein et al, 1997). Homologues of pb and cad genes have been reported in different taxa including sepiolid squids (Euprymna scolopes) (Callaerts et al, 2002) or abalones (Haliotis rufescens) (Degnan and Morse, 1993), but no cad or pb gene fragments have been reported in bivalve molluscs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation